Influence of underpasses and traffic on white‐tailed deer highway permeability - Norris L. Dodd; Jeffrey W. Gagnon (Wildlife Society Bulletin)
Abstract Highways constitute barriers to wildlife passage, or permeability, which fragment populations and habitats. The degree of barrier effect caused by roadways varies by wildlife species, highway type and standard, and traffic volume. We assessed deer–highway relationships along a 27‐km stretch of highway in central Arizona, USA. Our research objectives were to 1) assess white‐tailed deer (Odocoileus virginianus) highway crossing patterns and permeability, 2) compare deer permeability on 4‐lane reconstructed and 2‐lane control sections to determine the influence of wildlife underpasses, and 3) assess and compare deer passage relationships to traffic volume. We fitted 13 deer with Global Positioning System (GPS) collars between 2004 and 2007. Eleven deer crossed the highway 395 times. On 2 control sections, deer crossed an average of 0.02 times/day, while on 3 reconstructed sections they averaged 15 times more crossings/day (0.28; t13 = −2.35; P = 0.035). The deer passage rate on control sections averaged 0.03 crossings/approach, approximately 20% of that for reconstructed sections (0.16; t13 = −2.43; P = 0.030). We linked hourly traffic volumes to our GPS data to examine how passage rates and the proportion of deer relocations at different distances from the highway varied with traffic volume. Deer distance from the highway showed minimal shift away from the highway with increased traffic, and at‐grade passage rates were low (≤0.1 crossings/approach) across all traffic volumes. Although our linear regression analysis found no relationship between deer passage rate and increasing traffic volume on reconstructed sections with underpasses, there was a strong negative relationship on control sections (r = −0.881; P = 0.05); thus, we conclude that deer passage rates were minimally affected by traffic on reconstructed sections where passage structures facilitated below‐grade passage. Further, from the 865 deer groups we recorded on videotape at 5 underpasses, traffic levels did not affect below‐grade deer passage at the volumes we studied. Passage structures improved highway permeability across reconstructed sections with underpasses where traffic volume had a much lower impact compared to deer crossing at highway grade on control sections. © 2011 The Wildlife Society.